Comparison of two Phaeodactylum tricornutum ecotypes under nitrogen starvation and resupply reveals distinct lipid accumulation strategies but a common degradation process - Murison, Victor; Hérault, Josiane; Côme, Martine; Guinio, Sabrina; Lebon, Alexis; Chamot, Christophe; Bénard, Magalie; Galas, Ludovic; Schoefs, Benoît; Marchand, Justine; Bardor, Muriel; Ulmann, Lionel (Frontiers in Plant Science, 2023)
Phaeodactylum tricornutum is a model species frequently used to study lipid metabolism in diatoms. When exposed to a nutrient limitation or starvation, diatoms are known to accumulate neutral lipids in cytoplasmic lipid droplets (LDs). Those lipids are produced partly de novo and partly from the recycle of plastid membrane lipids. Under a nitrogen resupply, the accumulated lipids are catabolized, a phenomenon about which only a few data are available. Various strains of P. tricornutum have been isolated around the world that may differ in lipid accumulation patterns. To get further information on this topic, two genetically distant ecotypes of P. tricornutum (Pt1 and Pt4) have been cultivated under nitrogen deprivation during 11 days followed by a resupply period of 3 days. The importance of cytoplasmic LDs relative to the plastid was assessed by a combination of confocal laser scanning microscopy and cell volume estimation using bright field microscopy pictures. We observed that in addition to a basal population of small LDs (0.005 µm3 to 0.7 µm3) present in both strains all along the experiment, Pt4 cells immediately produced two large LDs (up to 12 µm3 after 11 days) while Pt1 cells progressively produced a higher number of smaller LDs (up to 7 µm3 after 11 days). In this work, we showed that lipid accumulation may be limited by the pre-starvation size of the plastid as a source of membrane lipids to be recycled, rather than by intracellular available space. After resupplying nitrogen and for both ecotypes, a fragmentation of the largest LDs was observed as well as a possible migration of LDs to the vacuoles, suggesting an autophagic degradation. Altogether, our results deepen the understanding of LDs dynamics and open research avenues for a better knowledge of lipid degradation in diatoms.